Animal-source foods: Their role in sustainable healthy diets - Leroy, Jef L.; Alonso, Silvia (International Food Policy Research Institute, 2024)
As part of the rapid evolution of diets in low- and middle-income countries (LMICs), consumption of animal-source foods (ASFs) has increased sharply in recent decades. This chapter examines ASFs as part of a sustainable healthy diet by exploring the beneficial role of ASFs in providing essential micronutrients in some age cohorts and populations in LMICs, the potential negative health impacts, and the environmental impacts associated with livestock production. It concludes with recommendations for ASF consumption, including policies and interventions for reducing excess consumption and promoting consumption where ASFs could play a larger role in sustainable healthy diets.